2019
DOI: 10.1101/569988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FAIM opposes stress-induced loss of viability and blocks the formation of protein aggregates

Abstract: A number of proteinopathies are associated with accumulation of misfolded proteins, which form pathological insoluble deposits. It is hypothesized that molecules capable of blocking formation of such protein aggregates might avert disease onset or delay disease progression. Here we report that Fas Apoptosis Inhibitory Molecule (FAIM) counteracts stress-induced loss of viability. We found that levels of ubiquitinated protein aggregates produced by cellular stress are much greater in FAIM-deficient cells and tis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…The expression and evolution pattern of faim and the related faim-Gm6432 gene suggested that FAIM might be involved more generally in cellular stress response pathways, rather than narrowly protecting against death receptor demise (Turner and Lysiak, 2008;Qiu et al, 2013;Durairajanayagam et al, 2015). This turned out to be correct and in the course of this work we found that loss of FAIM was associated with increased levels of stress-induced protein aggregation in FAIM-deficient cell lines and animals (Kaku and Rothstein, 2019). This raised the possibility that FAIM can act directly on dysfunctional proteins that aggregate.…”
Section: Introductionsupporting
confidence: 50%
See 4 more Smart Citations
“…The expression and evolution pattern of faim and the related faim-Gm6432 gene suggested that FAIM might be involved more generally in cellular stress response pathways, rather than narrowly protecting against death receptor demise (Turner and Lysiak, 2008;Qiu et al, 2013;Durairajanayagam et al, 2015). This turned out to be correct and in the course of this work we found that loss of FAIM was associated with increased levels of stress-induced protein aggregation in FAIM-deficient cell lines and animals (Kaku and Rothstein, 2019). This raised the possibility that FAIM can act directly on dysfunctional proteins that aggregate.…”
Section: Introductionsupporting
confidence: 50%
“…In this assay, large aggregated proteins are not able to pass through a 0.2 µm pore-sized filter, remain on the filter, and are blotted with anti-GFP antibody (Myeku et al, 2011). We found that much more aggregated mutant SOD1 was filter trapped in FAIM-deficient HeLa cells than in WT HeLa cells ( Figure 1D; Kaku and Rothstein, 2019). These results demonstrate the essential role of FAIM in blocking formation of mutant SOD1 aggregates.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations